Regional Disaggregation of Industrial Investment: The Case of Czech Regions - Zdražil Pavel; Kraftová Ivana (My University, 2016)
Properly structuring of industrial investment can increase the competitiveness and innovation potential of each region markedly; and results in welfare increasing. The intention of this study wasn’t evaluating the allocation of investment but develops the method of gaining the regional disaggregated data of industrial investment. Such data are valuable for further regional development analysis, nevertheless the two dimensional matrix of regional investment in industrial structure for many regions, i.e. Czech NUTS III regions is not available at the moment. The aim of this paper is to present the developed methodology of values estimation within the industrial structure at regional level; to verify this principle on the sample of Slovak regions and to apply the methodology on Czech regions over sixteen years period between 1995 and 2010. Due to many limitations and accuracy requirements of such an approach, the presented method cannot be applied to reliably disaggregation of whole regional industrial investment structure. Still we found an evidence to believe, that the method is applicable on the industries and industrial groups of construction; financial and insurance activities; trade, transportation, accommodation and food services; and public sector services.
Regionální desagregace odvětvových investic: příklad regionů ČR
Keywords: Industrial structure; Czech NUTS III regions; Slovak NUTS III regions; investment allocation; regional disaggregation; employment; odvětvová struktura; NUTS III regiony ČR; NUTS III regiony Slovenska; alokace investic; regionální desagregace; zaměstnanost